Reward and neurocomputational processes - Frank, Guido K W (Current topics in behavioral neurosciences, 2011)
The neurobiology of eating disorders (EDs) is largely unknown. However, brain imaging studies over the past decade have identified neurotransmitter alterations that could be part of dysfunctional behavior characteristics of EDs. In this chapter we focus on a specific behavioral construct, the brain reward system, and demonstrate a functional brain imaging approach toward identifying dopamine function in anorexia nervosa (AN). We demonstrate how human brain reward activation can be used in a translational approach to test whether computer models, based on basic science research, can predict expected in vivo reward system activation, and how such an approach can identify specific biologic alterations in a psychiatric population.